COVID-19 in rural Malawi: Perceived risks and economic impacts - Ambler, Kate; Herskowitz, Sylvan; Maredia, Mywish K.; Mockshell, Jonathan (International Food Policy Research Institute, 2020)
Malawi reported its first case of COVID-19 in April and declared a national emergency. Schools, bars and restaurants were closed, international flights suspended, and the economy faced considerable disruptions: quarterly growth projections from July were cut by more than 60% (Saldarriaga Noel et al. 2020). While still concerning, compared to other countries and other parts of the world, the spread of this disease in Malawi has been relatively modest with 5,951 confirmed cases and 184 COVID-19 linked deaths as of November 8, 2020. After accelerating rates of infection in June and July, the rates have decreased over the last two months. In response, there has been a partial return to normalcy, marked by easing COVID-19 restrictions and the reopening of schools at the beginning of September, even while the future trajectory of the disease remains unknown.